Nature and Causes of Locomotor Disabilities in India - Halder, Santoshi; Talukdar, Arindam (Journal of the American Academy of Special Education Professionals, 2013)
A large proportion of disability around the world is preventable. Levels of disability in many poor countries can be reduced by achieving the international development targets for economic, social and human development. In this paper, the author studied the different contributory and causative factors of locomotor disability, disease states and the significance of poverty in relation to disability in Eastern part of India. Final data were collected from 200 people with locomotor disability by personally visiting each individual and their family at their home or institutes on the basis of personal interviews, discussions with them, their parents and teachers. Data were collected by situational sampling technique and tools used for the study were General information schedule (GIS) and Semi-structured interview schedule. The study revealed that various diseases which resulted in locomotor disability in some way were related to poverty. The nature and causative factors for various diseases which resulted in locomotor disability are malnutrition, unhygienic condition in the pre-natal and postnatal period of the mother as well as carelessness of the medical practitioners. Among the other associated significant indirect causes has been found to be illiteracy, ignorance of the parents, and various socio-cultural issues. However, general improvements in living conditions will not be enough but an integrated and specific steps are required for prevention of disability, ensuring that people with disabilities are able to fully participate in the developmental process and claim their rights as well as obtain a fair share of the benefits as full and equal members of society.